On the Absolute Summability of Fourier Series of Almost Periodic Functions - Khasanov, Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We establish new sufficient conditions for the absolute |C, α|-summability of the Fourier series of functions almost periodic in a sense of Besicovitch whose spectrum has limit points at infinity and at the origin for \( α 12 \) .